Influence of coaxial air jet on mass diffusion of hydrogen jet injected through lobe-injector at supersonic flow. (5th October 2022) - Zhang, Ying-Fang; Musa, Awad
Abstract: The technique of fuel injection in the combustion chamber is crucial for increasing the performance of hypersonic vehicles. This study tries to investigate the mechanism of fuel injection and distribution when fuel and air are injected through coaxial lobe injectors. The main attention of this work is to present the mechanism of fuel mixing of transverse jet injected from various lobe injectors. Comparison of coaxial gets (air and fuel jet) with equivalent simple jet (fuel without air jet) is done to achieve an efficient model for the combustion chamber. In this work, finite-volume is used to simulate and study of fuel injection performance of a transverse hydrogen jet in different lobe injectors. 3-D flow visualizations are done to reveal the mechanism of the fuel penetration and streamline pattern for introduced models. Strength of circulation and fuel mixing efficiency are also investigated in the present work for 2-, 3-, and 4-lobe nozzles. Our outcomes indicate that the mixing performance of coaxial air and fuel jet injected through the 3-lobe nozzle is about 25% better than other nozzle types. Our findings confirm that injection of air jet through the core of the lobe nozzle increases fuel mixing up to 200% at the combustion chamber. Highlights: Impact of coaxial air and hydrogen jet on the fuel mixing of hydrogen jet is studied. 3-D computational model of hybrid injection system at supersonic combustion chamber is investigated. Effect of 2-lobe, 3-lobe and 4-lobe injectors with coaxial air jet on fuel mixing is totally explored. Injection of coaxial jet significantly increase fuel mixing of lobe injectors.